2020
DOI: 10.3758/s13421-019-01005-4
|View full text |Cite
|
Sign up to set email alerts
|

Need something different? Here’s what’s been done: Effects of examples and task instructions on creative idea generation

Abstract: Creative idea generation involves search and retrieval of memory. There is a default tendency to rely too heavily on familiar or easily accessible information during idea generation, especially in tasks such as the alternate uses task (AUT) that involve generating novel uses for common objects. Knowing which obvious ideas to avoid may be important in creating more original ideas. The present experiments tested whether instructions encouraging participants to avoid a set of common example ideas would enhance or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 63 publications
(141 reference statements)
1
19
1
Order By: Relevance
“…This may have had a limiting effect on their originality. Evidence for such a constraining effect can also be found in previous work of George and Wiley (2020) and Smith et al (1993) on the use of examples of alternative uses as part of the task instruction. In both studies, participants, upon performing the actual task, were found to search for alternative uses similar to the examples, resulting in less original responses.…”
Section: The Immediate Situation In Relation To Creativitymentioning
confidence: 61%
See 2 more Smart Citations
“…This may have had a limiting effect on their originality. Evidence for such a constraining effect can also be found in previous work of George and Wiley (2020) and Smith et al (1993) on the use of examples of alternative uses as part of the task instruction. In both studies, participants, upon performing the actual task, were found to search for alternative uses similar to the examples, resulting in less original responses.…”
Section: The Immediate Situation In Relation To Creativitymentioning
confidence: 61%
“…For example, to detect that a coffee mug can be used as a template to draw a circle, one needs to perceive that the cup can be traced around. The presentation modality may affect the perception of common and uncommon affordances (Chrysikou et al 2016;George and Wiley 2020). For example, Chrysikou et al (2016) have shown that participants were more likely to perceive common affordances when presented visual vs. verbal stimuli in an open-ended Alternative Uses Task.…”
Section: A Situated Approach To Creativitymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, instruction-scoring fit for creative quality and the original Guilford instruction would be slightly higher as compared to the fully unrestricted be-fluent instruction used in the current study. Instruction-scoring fit could even be further enhanced when instructions to avoid the most common use (Wilson et al, 1960) are further supplemented by commonly generated example ideas which are also required to be avoided (Shin et al, 2018; George and Wiley, 2019). Hence, it is yet unclear which degree of instruction-scoring fit (with explicit instructions to be creative representing maximum instruction-scoring fit when creative quality is of interest) is required for subjective ratings to be node-unidimensional.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most accessible information is often the least useful when aiming for originality. For example, exposure to common example ideas prior to generating one’s own ideas seems to heighten the accessibility of these ideas, which can subsequently diminish originality in creative thinking tasks (Cardoso & Badke-Schaub, 2011; George & Wiley, 2020; Smith et al, 1993). In this sense, activation arising from obvious ideas, initially retrieved information, or dominant associations can impede our ability to make creative connections between concepts.…”
mentioning
confidence: 99%